2019
DOI: 10.4103/jfmpc.jfmpc_430_18
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices regarding dietary supplements in Saudi Arabia

Abstract: Objective:The study was aimed at determining the characteristics and lifestyle choices of dietary supplement users and to assess knowledge, attitude, and practice related to dietary supplements in the health sciences students versus other individuals in Saudi Arabia.Methods:A descriptive cross-sectional, online questionnaire-based study was conducted on 351 participants (138 were health sciences students and 203 were not). The results were documented and analyzed using SPSS- version 22.Results:More than half o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
70
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 34 publications
(60 reference statements)
14
70
4
2
Order By: Relevance
“…A study conducted by Song et al [30] found that there was a significant correlation between the health condition being treated and the nature of vitamins and supplements being used. Srikanth et al [31] found that different groups consume vitamins and nutritional supplements for different reasons. As such, community pharmacists should have the right knowledge of vitamins and nutritional supplements in order to match the demands of the consumers.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Song et al [30] found that there was a significant correlation between the health condition being treated and the nature of vitamins and supplements being used. Srikanth et al [31] found that different groups consume vitamins and nutritional supplements for different reasons. As such, community pharmacists should have the right knowledge of vitamins and nutritional supplements in order to match the demands of the consumers.…”
Section: Discussionmentioning
confidence: 99%
“…10 In studies conducted with students studying in the field of health sciences, the rate has been shown to vary between 23% and 54%. 6,9,32,33 In the limited number of studies on dietary supplement use among students studying in health-related fields in Turkey, the prevalence of dietary supplement use varies between 10.7% and 18.5%. 7,8,12 The present study investigated In the current study, the most commonly used dietary supplements by the participants were vitamin B12, iron, and vitamin C. The vast majority of the participants stated that they benefited from dietary supplements, whereas one-fourth of them stated experiencing side effects caused by dietary supplements, the most common of which was weight gain.…”
Section: Ethical Approvalmentioning
confidence: 99%
“…6 Moreover, the prevalence of using these supplements among students ranges between 11% and 68% and it is reported that the majority of students use these supplements to be healthy. [7][8][9][10][11][12][13] In the literature, it is also reported that the use of dietary supplements is high in people with the symptoms of orthorexia nervosa (ON), followed by people with healthy eating and normal eating habits, respectively, that the rate of dietary supplement use for overall health is higher in people with healthy eating habits and ON symptoms than in people with normal eating habits and that the rate of dietary supplement use to increase energy, skin, hair, or nail health, digestive or urinary health, to improve mood, bone, joint, or muscle health and to enhance focus/concentration is higher in people with ON symptoms than in people with normal or healthy eating habits. 14 Healthy orthorexia is defined as "healthy interest in diet, healthy behavior with regard to diet, and eating healthily as part of one's identity."…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research data suggest that stress levels can be reduced through the consumption of dietary supplements, as well as also protecting against malnutrition [6][7][8]. According to scientific reports, the key reasons cited for taking supplements include ensuring adequate nutrition, maintaining good general health, improving physical appearance, and weight loss [9]. However, data are often inconclusive in this field, as the marketplace is completely flooded with dietary supplements which have no empirical evidence to support their usage [10].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization suggests that folic acid and iron supplements should be taken by women, particularly during pregnancy [1]. Vitamin D supplements are also very important in countries and societies where there is insufficient exposure to daylight; however, women must not consume excessive amounts of vitamin D, as this can cause further health issues; [2] renal complications can also be caused by consuming excessive quantities of calcium [9]. Liver problems and central nervous system problems are also associated with taking high doses of vitamin A [9].…”
Section: Introductionmentioning
confidence: 99%